(untitled) (Journal of the College of Basic Education, 2022)
The complexes of some lanthanide of trivalent (La, Nd, Gd and Dy) and tetravalent metal ion (Zr) with 1,1’bis-(ortho amino phenyl thio)-methane (L) have been synthesis and identified by elemental analysis (C.H.N.), FT-IR, UV-Vis spectra, conductivity measurements, atomic absorption and magnetic susceptibility. The complexes showed characteristic behaviour of octahedral geometry around the lanthanide ions with the (N, N, S) ligand coordinated in tridentate mode and the metal ion (Zr) with the (N, S). a, Kf, emax for complexes (Zr, La, Nd and Gd) were estimated. The study of biological activity of the ligand (L) and its complexes showed activity toward Staphylococcus laureus, Streptoccus pyogenes, Pseudomonas aeruginosa and E. coli